Pengembangan Aplikasi Pendaftaran Anggota Perpustakaan Berbasis Android menggunakan Model Waterfall pada Dinas Perpustakaan Kota Samarinda - Saputra, Muhammad Ramadhani; Rahim, Abdul; Suryawan, Sayekti Harits (Jurnal Informatika Terpadu, 2024)
Technology, especially smartphones, has become essential to daily life, providing quick access to various services and information. However, the Library and Archive Service of Samarinda City still uses manual member registration, which could be more efficient and time-consuming. This research addresses this issue by developing an Android-based library membership registration application using Flutter, Laravel, and MySQL. The Waterfall method and UML diagrams are used to structure the development process and model the system. The resulting application allows prospective members to register online, streamlines the registration process, and reduces the administrative burden on staff. A book search feature is also included, enabling members to check availability remotely. This saves time and reduces unnecessary visits to the library, improving user experience and overall library efficiency. Survey results show a high level of satisfaction, with an average percentage of 83%, indicating that most respondents agree with implementing this system.